Negative electrode for lithium secondary battery and method for manufacturing same

By applying a magnetic field on the negative electrode of the lithium secondary battery and controlling the rolling load according to the magnetic field strength, the problem of rebound of the negative electrode active layer is solved, and high energy density and battery life are improved.

CN119522489APending Publication Date: 2025-02-25LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480003341.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-13
Filing Date
2024-03-11
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The negative electrode active layer of the lithium secondary battery is prone to rebound after rolling, resulting in the thickness of the electrode active layer increasing over time, thereby reducing the energy density.

Method used

The rolling load is determined by drying and rolling the negative electrode slurry with the application of a magnetic field and controlling the rolling load according to the strength of the applied magnetic field, using the formula y = Ax + B (where -0.01 ≤ A < 0 and 3 ≤ B ≤ 7) to suppress rebound.

Benefits of technology

The rebound phenomenon of the negative electrode active layer is effectively suppressed, the predetermined thickness is maintained, the energy density of the electrode is increased, and the life of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522489A_ABST
    Figure CN119522489A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode of a lithium secondary battery and a method for manufacturing the same. The method of manufacturing a negative electrode includes drying a negative electrode slurry to which a magnetic field is applied, then rolling the dried negative electrode slurry, controlling a rolling load according to Equation 1 depending on the strength of the magnetic field applied to the negative electrode slurry, and thus significantly reducing springback of a negative electrode active layer even if the process is simple and less, and improving the reliability of the negative electrode. As a result, excellent treatment efficiency and economic efficiency are achieved. In addition, the manufactured negative electrode exhibits a high energy density while maintaining a target thickness, and reduces charge / discharge-related volume variation of the negative electrode active layer due to low rolling stress and improved structural stability of the negative electrode active layer, thereby advantageously improving its lifespan.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2023-0032292, filed on Mar. 13, 2023, which is hereby incorporated by reference in its entirety.

[0002] The present disclosure relates to a negative electrode of a lithium secondary battery and a method for manufacturing the same. Background Art

[0003] Recently, secondary batteries are widely used not only in small devices such as portable electronic devices but also in medium and large devices such as battery packs or power storage devices in hybrid electric vehicles or electric vehicles.

[0004] Among them, lithium secondary batteries are manufactured by using metal oxides such as LiCoO2 as positive electrode active materials and carbon materials as negative electrode active materials, a porous separator of polyolefin type between the negative electrode and the positive electrode, and a non-aqueous electrolyte containing lithium salts such as LiPF6. During charging, the lithium ions in the positive electrode active material are released and inserted into the carbon layer of the negative electrode, and conversely, during discharge, the lithium ions in the negative electrode carbon layer are released and inserted into the positive electrode active material. In this case, the non-aqueous electrolyte that penetrates into the positive and negative electrodes acts as a medium for the movement of lithium ions between the negative and positive electrodes.

[0005] In order to realize such a high-capacity and high-energy-density lithium secondary battery, it is necessary to increase the load amount of each electrode, and further it is necessary to increase the rolling density during electrode production.

[0006] Specifically, the electrode of the lithium secondary battery can be obtained as an electrode sheet, wherein the electrode sheet can be dried by applying an electrode slurry including an electrode active material to an electrode current collector at a high load during manufacturing, and the dried electrode slurry can be rolled and formed by a rolling device to form a high-load and high-density electrode active layer on the electrode current collector. Here, when manufacturing the sheet after rolling, the rolling is performed in consideration of the density distribution, thickness, thickness distribution, precision, etc. of the desired electrode active layer.

[0007] However, due to the stress accumulated in the powder of the electrode active material contained in the electrode active layer when the electrode active layer is pressurized during rolling, the sheet after rolling tends to return to the original state, in other words, a serious springback phenomenon occurs. Therefore, over time, the thickness of the electrode active layer including the electrode active material becomes thicker than the desired thickness. This causes the problem of reduced energy density of the electrode with a high load.

[0008] In order to improve the above springback phenomenon, a technology of rolling the dried electrode slurry multiple times or rolling the dried electrode slurry by using a multi-stage rolling device has been developed. However, the technology not only cannot completely suppress the springback phenomenon, but also has the limitation of low economic feasibility in terms of energy or processing efficiency.

[0009] Therefore, there is an urgent need for an electrode manufacturing technology that can solve the above problems and maintain a desired target thickness despite the lapse of time after rolling. Summary of the invention

[0010] Technical issues

[0011] An object of the present disclosure is to provide a negative electrode of a lithium secondary battery and a method for manufacturing the same, wherein the springback phenomenon of an active layer (especially, an active layer having a high load) is suppressed, thereby maintaining a desired target thickness despite the lapse of a predetermined time during rolling.

[0012] Technical Solution

[0013] In order to solve the above problems,

[0014] In one embodiment, the present disclosure provides a method for manufacturing a negative electrode of a lithium secondary battery, the manufacturing method comprising the following steps:

[0015] applying a magnetic field to the negative electrode slurry applied to the negative electrode current collector;

[0016] drying the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; and

[0017] rolling the formed negative electrode active layer,

[0018] Wherein, the negative electrode slurry includes a carbon-based negative electrode active material,

[0019] wherein the magnetic field is applied at a strength of 3,000G to 15,000G,

[0020] The rolling load during rolling is controlled according to the following formula 1:

[0021] [Formula 1]

[0022] y=Ax+B

[0023] In formula 1,

[0024] y represents the rolling load (unit: tons),

[0025] x indicates the magnetic field strength when the magnetic field is applied (unit: Gauss),

[0026] A and B are -0.01≤A<0 and 3≤B≤7.

[0027] In this case, the rolling load may be 1 ton to 7 tons.

[0028] In addition, the rolling may include: a first rolling, in which the formed negative electrode active layer is pressurized using a rolling load of [Formula 1]; and a second rolling, in which the negative electrode active layer after the first rolling is further pressurized, wherein the rolling load of the first rolling may be greater than the rolling load of the second rolling.

[0029] Specifically, the rolling load of the second rolling may be a ratio of 50% or less of the rolling load of the first rolling.

[0030] In addition, the rolling may be performed at a temperature of 20°C to 35°C.

[0031] As such, the negative electrode active layer may have an average thickness increase rate of less than 10% after rolling for 72 hours at room temperature based on an average thickness immediately after rolling.

[0032] Furthermore, the magnetic field application may be performed for 5 seconds to 60 seconds.

[0033] Furthermore, in one embodiment, the present disclosure includes:

[0034] a negative electrode current collector; and a negative electrode active layer disposed on at least one surface of the negative electrode current collector and comprising a carbon-based negative electrode active material,

[0035] A negative electrode of a lithium secondary battery manufactured by the manufacturing method according to the present disclosure as described above is provided.

[0036] In this case, the negative electrode active layer may have an alignment degree (OI) of a carbon-based negative electrode active material represented by Formula 2, the alignment degree being 0.2 to 1.5:

[0037] [Formula 2]

[0038] OI=I 004 / I 110

[0039] In formula 2,

[0040] I 004 indicates the area of ​​the peak representing the (0,0,4) crystal plane in the X-ray diffraction spectrum measurement of the negative electrode active layer, and

[0041] I 110 Indicates the area of ​​the peak representing the (1,1,0) crystal plane in the X-ray diffraction spectrum measurement of the negative electrode active layer.

[0042] In addition, the density of the negative electrode active layer can be 1.2 g / cm 3 Up to 1.8g / cm 3 , and the average thickness may be 100 μm to 300 μm.

[0043] In addition, the rebound rate of the negative electrode active layer may be less than 10%.

[0044] In addition, the carbon-based negative electrode active material included in the negative electrode active layer may include at least one of natural graphite and artificial graphite.

[0045] In addition, in some cases, the negative electrode active layer may further include a silicon-based negative electrode active material, and the silicon-based negative electrode active material block may include Si, SiC and SiO. x At least one of (wherein 0.8≤x≤2.5).

[0046] Beneficial Effects

[0047] According to the present invention, a method for manufacturing a negative electrode of a lithium secondary battery is to dry a negative electrode slurry and then roll it while applying a magnetic field, but by controlling the rolling load according to Formula 1 which depends on the strength of the magnetic field applied to the negative electrode slurry, the method is simple and effective in improving the rebound phenomenon of the negative electrode active layer even with a small amount of treatment.

[0048] In addition, the manufactured negative electrode not only exhibits high energy density while maintaining the target thickness even when the load of the negative electrode active layer is large, but also has the advantages of low rolling stress and improved structural stability of the negative electrode active layer, which suppresses the volume change of the negative electrode active layer according to charging and discharging, thereby improving the life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is an image illustrating the crystal phase of graphite (carbon-based negative electrode active material) and an axial view showing the maximum expansion of graphite crystals due to a springback phenomenon during rolling.

[0050] Figure 2 is a graph illustrating a rolling load applied according to a magnetic field intensity during manufacturing of a negative electrode according to Formula 1 according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0051] The present disclosure may have various modified forms and various embodiments, so specific embodiments thereof will be described in detail below.

[0052] However, it should be understood that the present disclosure is not limited to these specific embodiments, and includes all modifications, equivalents, or substitutes within the spirit and technical scope of the present disclosure.

[0053] The terms "include", "comprising" and "having" are used herein to specify the presence of characteristics, numbers, steps, actions, parts or components, or a combination thereof, described in the specification, and it should be understood that the possibility of the presence or addition of one or more other characteristics, numbers, steps, actions, parts, components, or a combination thereof is not precluded.

[0054] In addition, in the present disclosure, when a portion of a layer, film, region, plate, etc. is disposed "on" another portion, this includes not only a case where one portion is disposed "directly" "on" another portion, but also a case where another portion is interposed between them. Conversely, when a portion of a layer, film, region, plate, etc. is disposed "under" another portion, this includes not only a case where one portion is disposed "directly" "under" another portion, but also a case where another portion is interposed between them. In addition, in the present application, "on" may include not only a case where it is disposed on an upper portion, but also a case where it is disposed on a lower portion.

[0055] In addition, in the present disclosure, "including as a main component" may mean including at least 50% by weight (or at least 50% by volume), at least 60% by weight (or at least 60% by volume), at least 70% by weight (or at least 70% by volume), at least 80% by weight (or at least 80% by volume), at least 90% by weight (or at least 90% by volume), or at least 95% by weight (or at least 95% by volume) of the defined component relative to the total weight (or total volume) of the negative electrode active material. For example, "including graphite as a main component of the negative electrode active material" may mean including at least 50% by weight, at least 60% by weight, at least 70% by weight, at least 80% by weight, at least 90% by weight, or at least 95% by weight of graphite based on the total weight of the negative electrode active material, and in some cases, may mean that the entire negative electrode active material is graphite, including at least 100% by weight of graphite.

[0056] In addition, as used herein, “electrode sheet” may refer to an object to which a negative electrode current collector is applied with a negative electrode slurry, or an object to which a negative electrode current collector is applied with a negative electrode slurry that forms a negative electrode active layer after drying.

[0057] In addition, as used herein, "carbon-based negative electrode active material orientation" or "carbon-based negative electrode active material alignment" means that the crystal planes of the carbon-based negative electrode active material including the negative electrode active material particles are distributed in a predetermined orientation relative to the surface of the negative electrode current collector. In this case, the crystal plane is a crystal plane representing the planar structure of the carbon-based negative electrode active material, which may mean a (1,0,0) crystal plane or a (1,1,0) crystal plane. In addition, "orienting the carbon-based negative electrode active material" may be different from the carbon-based negative electrode active material particles themselves being arranged to have a specific orientation within the negative electrode active layer.

[0058] In addition, "high orientation (or degree of orientation) of carbon-based negative electrode active materials" may mean that the carbon-based negative electrode active materials contained in the negative electrode active layer are aligned at a high frequency relative to the surface of the negative electrode collector, and in some cases, it may mean that the carbon-based negative electrode active materials contained in the negative electrode active layer are aligned at a high angle (for example, greater than 45°; more specifically, 60° or greater) relative to the surface of the negative electrode collector.

[0059] In addition, "a high degree of alignment of the carbon-based negative electrode active material" may mean that "OI" referred to herein has a large value, so that the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a low angle (e.g., less than 45°) relative to the surface of the negative electrode current collector. Conversely, "a low degree of alignment of the carbon-based negative electrode active material" may mean that "OI" has a small value, indicating that the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., greater than 45°; more specifically, greater than 60° or more) based on the surface of the negative electrode current collector.

[0060] In addition, as used in this article, the term "crystal plane of carbon-based negative electrode active material" may refer to the surface of the atoms of the carbon-based negative electrode active material forming a crystal shape, and in the present disclosure may mean a crystal plane including the plane of the carbon-based negative electrode active material or a crystal plane including the a-axis / ab-axis of the carbon-based negative electrode active material crystal.

[0061] Hereinafter, the present disclosure will be described in more detail.

[0062] Method for manufacturing negative electrode of lithium secondary battery

[0063] In one embodiment, the present disclosure provides a method for manufacturing a negative electrode of a lithium secondary battery, the manufacturing method comprising the following steps:

[0064] applying a magnetic field to the negative electrode slurry applied to the negative electrode current collector (S1);

[0065] drying the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer (S2); and

[0066] The formed negative electrode active layer is rolled (S3).

[0067] The manufacturing method of the negative electrode according to the present disclosure includes: applying a negative electrode slurry including a carbon-based negative electrode active material to a negative electrode current collector, and applying a magnetic field to the surface of the applied negative electrode slurry (S1) to align the carbon-based negative electrode active material in the negative electrode slurry to have a predetermined angle relative to the surface of the negative electrode current collector. Subsequently, the negative electrode slurry can be dried to form a negative electrode active layer (S2) including a highly oriented carbon-based negative electrode active material, and the negative electrode can be manufactured by rolling the continuously formed negative electrode active layer (S3).

[0068] In this case, the present disclosure can effectively improve the springback phenomenon of the negative electrode active layer after rolling by controlling the rolling load of the negative electrode active layer according to the intensity of the magnetic field applied to the negative electrode slurry.

[0069] Generally, the negative electrode of a lithium secondary battery is manufactured by rolling a negative electrode sheet having a negative electrode active layer thereon with a rolling device to increase the energy density. However, the problem with the rolled sheet is that the thickness of the negative electrode active layer becomes thicker than the desired thickness over time because the negative electrode active material attempts to return to its original state (in other words, a rebound phenomenon) due to the stress accumulated in the negative electrode active material powder when the rolling is performed. This phenomenon is strongly manifested with an increase in the load amount, which represents the weight of the negative electrode active material per unit surface area or unit volume of the negative electrode active layer.

[0070] In order to improve such a problem, it is necessary to perform multiple rolling processes or perform a complex rolling process such as a multi-stage rolling process. However, even if multiple rolling processes or a complex rolling process such as a multi-stage rolling process are performed, the rebound improvement effect is significantly reduced after a predetermined period of time, and there is a limitation that the rebound improvement effect is not obvious as the load amount of the negative electrode active material increases.

[0071] In contrast, the method for manufacturing a negative electrode according to the present disclosure can also exhibit a high springback improvement effect by controlling the rolling load according to the following Formula 1 depending on the strength of the magnetic field applied to the negative electrode slurry, although the rolling process is performed no more than twice (more specifically, only once):

[0072] [Formula 1]

[0073] y=Ax+B

[0074] In formula 1,

[0075] y represents the rolling load (unit: tons),

[0076] x indicates the magnetic field strength when the magnetic field is applied (unit: Gauss),

[0077] A and B satisfy -0.01≤A<0 and 3≤B≤7.

[0078] Hereinafter, the method for manufacturing a negative electrode according to the present disclosure will be described in more detail in each step.

[0079] First, the negative electrode manufacturing method according to the present disclosure includes a step (S1) of applying a magnetic field to the negative electrode slurry applied to the negative electrode current collector. The step (S1) refers to orienting the crystal plane of the carbon-based negative electrode active material contained in the negative electrode slurry to have a predetermined angle relative to the negative electrode current collector to suppress the rebound phenomenon of the carbon-based negative electrode active material after rolling.

[0080] For example, in the case of graphite among carbon-based negative electrode active materials, it has a two-dimensional plane such as Figure 1 In the three-dimensional space where the crystal phase of graphite exists, the directions in which the planes of graphite are located become the a-axis and the b-axis, and the direction in which the planes are stacked becomes the c-axis direction. When pressure is applied to such graphite, the graphite returns to the original state due to the stress accumulated in the crystal phase, and wherein, when pressure is applied in the c-axis direction of the crystal phase, the expansion due to recovery is the largest.

[0081] The present disclosure overcomes this problem through the following steps: before the negative electrode slurry is dried, the crystal plane is aligned in the c-axis direction of the carbon-based negative electrode active material contained in the negative electrode slurry so that the crystal plane is horizontal to the negative electrode collector. In other words, the plane of the carbon-based negative electrode active material is perpendicular to the negative electrode collector, so as to suppress the rebound phenomenon of the carbon-based negative electrode active material after the negative electrode active layer is rolled.

[0082] Here, the orientation of the carbon-based negative electrode active material can be performed by applying a magnetic field to the negative electrode slurry applied to the pre-dried negative electrode collector. In other words, the step of applying the magnetic field can be performed by setting a magnetic component in the upper and lower parts of the negative electrode collector (which moves due to the application of the negative electrode slurry to the surface).

[0083] In addition, since the degree of orientation of the carbon-based negative active material can be controlled by the intensity of the magnetic field applied to the negative electrode slurry or the time of exposure to the magnetic field, the magnetic field application can be performed under predetermined magnetic field intensity and time conditions.

[0084] Specifically, the power supply can be 3,000G (Gauss) to 15,000G, more specifically, 3,000G to 12,000G; 3,000G to 11,000G; 3,000G to 10,000G; 3,000G to 9,000G; 3,000G to 8,000G; 3,000G to 7,500G; 3,000G to 6,000G; 5,000G to 9,000G; 10, The magnetic field is applied by a magnetic field of 000g to 15,000G; 8,000G to 12,000G; 3,000G to 12,000G; 4,000G to 8,000G; 5,000G to 8,500G; 3,000G to 5,500G; 3,500G to 5,500G; 4,000G to 5,500G; 3,500G to 4,500G; or 4,500G to 5,000G.

[0085] In addition, applying the magnetic field can be performed for a period of 5 seconds to 60 seconds, and more specifically, can be performed for a period of 5 seconds to 30 seconds; 10 seconds to 60 seconds; 10 seconds to 30 seconds; 30 seconds to 60 seconds; 40 seconds to 50 seconds; 15 seconds to 35 seconds; 10 seconds to 50 seconds; or 20 seconds to 40 seconds.

[0086] The present disclosure can easily orient the crystal plane of the carbon-based negative electrode active material contained in the negative electrode slurry to a high angle close to vertical with respect to the surface of the negative electrode collector by applying a magnetic field of the magnitude and duration described above.

[0087] In addition, the method for manufacturing the negative electrode according to the present disclosure includes the step of drying the negative electrode slurry in which the carbon-based negative electrode active material is oriented by applying a magnetic field to form the negative electrode active layer S2 .

[0088] Here, the drying of the negative electrode slurry can be applied in any manner that can maintain the orientation of the carbon-based negative electrode active material contained in the negative electrode active layer without particular limitation. For example, the drying can be performed by applying heat energy to the negative electrode slurry using a hot air dryer, a vacuum oven, etc.

[0089] In addition, the negative electrode manufacturing method according to the present disclosure includes manufacturing the negative electrode by rolling the formed negative electrode active layer (S3). This step (S3) can be performed by a method conventionally used in the art such as a rolling press to increase the density of the negative electrode active layer.

[0090] In this case, the load applied to the negative electrode active layer during rolling is controlled according to the following Formula 1 depending on the intensity of the magnetic field applied to the negative electrode slurry:

[0091] [Formula 1]

[0092] y=Ax+B

[0093] In formula 1,

[0094] y represents the rolling load (unit: tons),

[0095] x indicates the magnetic field strength when the magnetic field is applied (unit: Gauss),

[0096] A and B satisfy -0.01≤A<0 and 3≤B≤7.

[0097] Formula 1 is a parameter indicating the correlation between the strength of the magnetic field applied to the negative electrode slurry and the load applied to the negative electrode active layer during rolling. Wherein, A and B in the above formula 1 are constants, wherein A may be at least -0.1 and less than zero (in other words, -0.1≤A<0), more specifically, at least -0.01 and less than zero (i.e., -0.01≤A<0); at least -0.001 but less than zero (i.e., -0.001≤A<0); -0.001 to -0.000001 (i.e., -0.001≤A≤-0.000001); or -0.0005 to -0.000001 (i.e., -0.0005≤A≤-0.000001). In addition, B can be 3 to 7 (i.e., 3≤B≤7), more specifically 4 to 6 (i.e., 4≤B≤6); 4.1 to 4.9 (i.e., 4.1≤B≤4.9); 5.1 to 5.9 (i.e., 5.1≤B≤5.9); or 4.5 to 5.7 (i.e., 4.5≤B≤5.7).

[0098] In the above formula 1, "load" refers to the force applied to the surface of the negative electrode active layer itself, and since the negative electrode active layer is subjected to the load when it is transported during the rolling process, the "pressure applied during rolling" should be reflected in the length in the direction perpendicular to the direction in which the negative electrode active layer is transported (in other words, the width direction length of the negative electrode active layer). For example, if the negative electrode slurry is applied to the current collector using a die-coater with a coating width of 26.2 cm, the negative electrode active layer (length in the width direction: 26.2 cm) formed by drying the negative electrode slurry is to be rolled with a rolling load of 5 tons, and the preload may be about 0.19 tons / cm.

[0099] According to the above formula 1, when the intensity of the magnetic field applied to the negative electrode slurry increases, the rolling load can be reduced. This means that the rolling load required to suppress the rebound phenomenon of the negative electrode active layer is affected by the orientation degree of the carbon-based negative electrode active material, and the orientation of the carbon-based negative electrode active material is affected by the intensity of the magnetic field applied to the negative electrode slurry. The present disclosure controls the rolling load of the negative electrode active layer according to the present disclosure so that the rolling process is performed no more than twice (more specifically, only once), and can show a high rebound improvement effect.

[0100] When rolling with a load according to the above formula 1, the present disclosure also provides that it is not necessary to apply an excessively high load to the negative electrode active layer in order to improve the rebound phenomenon, so that the rolling stress applied to the manufactured negative electrode can be significantly reduced, and the structural stability of the negative electrode active layer can be obtained. In addition, the present disclosure can provide the possibility of developing and / or manufacturing a negative electrode with a thinner thickness, because the rolling of the negative electrode active layer is possible even under a relatively low load, which allows for subsequent application of additional external forces (e.g., rolling loads, etc.) without applying excessive stress to the negative active layer. In addition, a negative electrode with a smaller thickness can be advantageous in terms of charge and discharge capacity, power and / or energy density, because many electrodes can be stacked in an electrode assembly under the same thickness conditions.

[0101] As an example, the negative electrode active layer of the negative electrode manufactured according to the present disclosure can have an average thickness increase rate of less than 4% based on the average thickness just after rolling after rolling for 2.5 hours at room temperature (22±1°C), and more specifically, the average thickness increase rate can be less than 3%; less than 2%; or less than 1.5%.

[0102] As another example, the negative electrode active layer of the negative electrode manufactured according to the present disclosure can have an average thickness increase rate of less than 10% based on the average thickness just after rolling after rolling for 72 hours at room temperature (22±1°C), and more specifically, the average thickness increase rate can be 9.5% or less; or 9% or less.

[0103] In the present disclosure, as described above, rolling may be performed only once, and in some cases, rolling may be performed twice. In this case, rolling the negative electrode active layer may include a first rolling (S3-1) of pressurizing the dried negative electrode active layer and a second rolling (S3-2) of further pressurizing the negative electrode active layer after the first rolling.

[0104] Specifically, the first rolling (S3-1) can be a rolling step that increases the energy density of the negative electrode active layer after drying, so that the density of the negative electrode active layer is significantly increased. Therefore, the first rolling (S3-1) can be performed with a load equal to the load in the case of performing only one rolling, and the rolling load can be controlled according to Formula 1.

[0105] In addition, the second rolling (S3-2) may be a step of further pressurizing the negative electrode active layer after the first rolling to compensate for the slightly occurring rebound phenomenon of the negative electrode active layer while improving the surface properties of the negative electrode current collector and the negative electrode active layer. Therefore, the second rolling (S3-2) may be less than the rolling load applied to the negative electrode active layer during the first rolling. Specifically, the rolling load during the second rolling may have a ratio of 50% or less of the rolling load during the first rolling, and more specifically, the rolling load during the second rolling may have a ratio of 45% or less of the rolling load during the first rolling; 40% or less; 35% or less; 20% or less; 20% to 45%; 25% to 45%; or 30% to 45%.

[0106] In addition, the rolling load of the negative electrode active layer may be 1 ton to 7 tons, more specifically, 1 ton to 3 tons; 2 tons to 6 tons; 3 tons to 7 tons; 4 tons to 7 tons; or 4.5 tons to 5.9 tons.

[0107] The load may be a load when one rolling loading is performed on the negative electrode active layer, and in some cases, the load may be a load applied at the first rolling when two rolling loadings are performed. The present disclosure can increase the density of the negative electrode active layer by performing rolling loading in the range as described above and preventing the crystal plane alignment of the carbon-based negative electrode active material from being reduced and thus preventing the rebound phenomenon from being improved.

[0108] In addition, when the above rolling (S3) is performed, the temperature and the rolling speed may satisfy a predetermined range.

[0109] Specifically, rolling (S3) when performed may be performed at a temperature below 40°C, and more specifically, rolling (S3) may be performed at a temperature of 20°C to 30°C; 20°C to 28°C; 25°C to 30°C; or 22°C to 24°C.

[0110] In addition, rolling (S3) can be carried out at a rolling speed of 2m / s to 7m / s, more specifically, 2m / s to 6.5m / s; 2m / s to 6m / s; 2m / s to 5.5m / s; 2m / s to 5m / s; 2m / s to 4.5m / s; 2m / s to 4m / s; 2.5m / s to 4m / s; 2.5m / s to 3.5m / s; 3.5m / s to 5m / s; 5m / s to 7m / s; 5.5m / s to 6.5m / s or 6m / s to 7m / s.

[0111] The present disclosure can increase the energy density of the negative electrode while minimizing the change in the alignment degree of the carbon-based negative electrode active material included in the negative electrode active layer formed by rolling the dried negative electrode slurry under the above temperature conditions and / or speed conditions.

[0112] In addition, in the present disclosure, the negative electrode slurry may be applied to the negative electrode current collector by discharging and coating the negative electrode slurry containing the carbon-based negative electrode active material on the surface of the moving negative electrode current collector. Here, the application method may be a die coating method.

[0113] The die coating method can be performed using a slit die with a gasket for controlling the discharge conditions of the negative electrode slurry. In this case, by controlling the shape of the gasket, etc., the load amount, application thickness, etc. of the negative electrode slurry applied to the negative electrode collector can be easily controlled.

[0114] The manufacturing method of the negative electrode of the lithium secondary battery according to the present disclosure has the configuration as described above, and therefore has excellent processability and economic feasibility, because even without performing complex rolling treatments such as multiple rolling or multi-stage rolling as in conventional methods, the rebound phenomenon of the negative electrode active layer can be significantly improved with simple and small amounts of treatment.

[0115] Negative electrode of lithium secondary battery

[0116] In one embodiment, the present disclosure also provides

[0117] A negative electrode of a lithium secondary battery manufactured by the method according to the present disclosure as described above, the negative electrode comprising:

[0118] A negative electrode current collector; and a negative electrode active layer disposed on at least one surface of the negative electrode current collector and comprising a carbon-based negative electrode active material.

[0119] The negative electrode of the lithium secondary battery according to the present disclosure includes a negative electrode active layer, which includes a carbon-based negative electrode active material located on at least one surface of a negative electrode current collector. The negative electrode active layer, which is a layer that implements the electrical activity of the negative electrode, is manufactured by the following steps: applying a negative electrode slurry including a negative electrode active material that practices an electrochemical oxidation-reduction reaction during battery cell charging and discharging to at least one surface of the negative electrode current collector, and then drying and rolling the negative electrode slurry.

[0120] Typically, the negative electrode of a lithium secondary battery is manufactured by rolling a negative electrode sheet having a negative electrode active layer thereon with a rolling device in order to increase the energy density. However, the problem with the rolled sheet is that the thickness of the negative electrode active layer becomes thicker than the desired thickness over time, because when rolling is performed, the accumulated stress in the negative electrode active material powder causes the negative electrode active material to tend to return to its original state (i.e., rebound phenomenon). This phenomenon is more intense as the load amount indicating the weight of the negative electrode active material per unit surface area or unit volume of the negative electrode active layer increases. To improve this problem, it is necessary to perform multiple rolling or perform a complex rolling process such as a multi-stage rolling process.

[0121] However, the negative electrode according to the present disclosure is characterized in that, by controlling the rolling load according to Formula 1, after rolling the negative electrode slurry (the negative electrode slurry is formed after applying a magnetic field to the negative electrode slurry by the above-mentioned manufacturing method according to the present invention), the rebound phenomenon of the negative electrode active layer is significantly improved. Therefore, the negative electrode has the advantages of high energy density of the negative electrode active layer and high processability and economic feasibility during manufacturing. In addition, the negative electrode has the advantages of high structural stability of the negative electrode active layer and low rolling stress, so that the volume change of the negative electrode active layer according to charging and discharging is reduced, thereby improving the life of the battery.

[0122] In the present invention, the negative electrode active layer includes a carbon-based negative electrode active material as a negative electrode active material to achieve electrical activity using a reversible redox reaction during battery charge and discharge.

[0123] The carbon-based negative electrode active material means a material having carbon atoms as a main component, and such a carbon-based negative electrode active material may include graphite. The graphite may include one or more of natural graphite and artificial graphite.

[0124] In one example, the carbon-based negative electrode active material may include mixed graphite as a mixture of natural graphite and artificial graphite. In this case, the mixed graphite may be a mixture of natural graphite and artificial graphite in a weight ratio of 10 to 50:50 to 90 or 10 to 30:70 to 90. By adjusting the content ratio of natural graphite to artificial graphite as above, the mixed graphite can prevent the adhesion of the negative electrode current collector to the negative electrode active layer from being reduced due to less than 10 parts by weight of natural graphite relative to the total weight, and can prevent the charge and discharge capacity of the negative electrode from being reduced due to more than 50 parts by weight of natural graphite.

[0125] In addition, conventional artificial graphite has an excellent effect on improving the life characteristics of the battery, but because its capacity is low compared to natural graphite, a higher load is required to manufacture a high-density electrode. However, since the rolling properties of artificial graphite are low and the rebound phenomenon is strong, it is difficult to manufacture a high-density electrode that meets the desired thickness. However, the negative electrode of the present invention can be manufactured by the manufacturing method of the present invention, thereby providing a high-density negative electrode active layer that suppresses the rebound phenomenon even if the artificial graphite content included in the carbon-based negative electrode active material is high.

[0126] In addition, the shape of the carbon-based negative electrode active material is not particularly limited, but preferably has the shape of a spherical graphite aggregate formed by aggregating a plurality of flake graphites. As flake graphite, in addition to natural graphite, artificial graphite, tar and asphalt-based mesophase calcined carbon (blocky mesophase), coke (green coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc. are graphitized. In particular, the above carbon-based negative electrode active materials are preferably assembled using a plurality of highly crystalline natural graphites. In addition, a graphite aggregate can be formed by aggregating 2 to 100 sheets (preferably 3 to 20 sheets) of graphite into a flake shape.

[0127] In addition, the above carbon-based negative electrode active materials may have an average particle size (D 50 ), and more specifically, may exhibit an average particle size (D) of 0.5 μm to 15 μm; 0.5 μm to 10 μm; 5 μm to 20 μm; 10 μm to 20 μm; 12 μm to 18 μm; 2 μm to 7 μm; 0.5 μm to 5 μm; or 1 μm to 3 μm. 50 ).

[0128] The average particle size of graphite may advantageously have a smaller particle size to maximize the degree of disorder of each particle in the expansion direction to prevent the particles from expanding due to the charging of lithium ions. However, when the particle size of graphite is less than 0.5 μm, a large amount of binder may be required due to the increase in the number of particles per unit volume. On the other hand, when the maximum particle size exceeds 20 μm, the expansion becomes serious, and with repeated charging and discharging, the binding properties between the particles and the binding properties of the particles to the current collector are reduced, and the cycle characteristics are greatly reduced.

[0129] In addition, the negative electrode active layer may have a predetermined range of loading, which indicates the weight of the carbon-based negative electrode active material per unit surface area / volume. As an example, the negative electrode active layer may have 250 mg / 25 cm 2 Up to 500mg / 25cm 2 Specifically, the negative electrode active layer may have a loading of 250 mg / 25 cm 2 Up to 450mg / 25cm 2 ; 250mg / 25cm 2 Up to 400mg / 25cm 2 ; 250mg / 25cm 2 Up to 350mg / 25cm 2 ; 250mg / 25cm 2 Up to 300mg / 25cm 2 ; 270mg / 25cm 2 Up to 380mg / 25cm 2; 300mg / 25cm 2 Up to 500mg / 25cm 2 ; 380mg / 25cm 2 Up to 450mg / 25cm 2 ; or 400mg / 25cm 2 Up to 500mg / 25cm 2 The present disclosure can achieve high capacity and high power output of the manufactured lithium secondary battery by adjusting the load of the negative electrode active layer to the above range.

[0130] In addition, the negative electrode active layer may include such a carbon-based negative electrode active material, in which the crystal plane is aligned at a high angle close to perpendicular to the negative electrode current collector due to the application of a magnetic field before the negative electrode slurry is dried. In the case of graphite among carbon-based negative electrode active materials, by aligning the crystal plane in the a-axis and b-axis directions in the three-dimensional space where the plane of the graphite exists (wherein the crystal phase of the graphite exists close to perpendicular to the negative electrode current collector), the rebound phenomenon caused by rolling can be significantly improved, and the structural stability can be improved, so that the volume change of the negative electrode active layer according to charging and discharging can be reduced.

[0131] In one example, the above negative electrode active layer may be oriented such that the crystal plane of the carbon-based negative electrode active material is oriented such that the degree of alignment (OI) represented by the following Formula 2 satisfies a predetermined value:

[0132] [Formula 2]

[0133] OI=I 004 / I 110

[0134] In formula 2,

[0135] I 004 indicates the area of ​​the peak representing the (0,0,4) crystal plane in the X-ray diffraction spectrum (XRD) measurement of the negative electrode active layer, and

[0136] I 110 Indicates the area of ​​the peak indicating the (1,1,0) crystal plane in X-ray diffraction spectrum (XRD) measurement of the negative electrode active layer.

[0137] The crystal plane orientation of the carbon-based negative electrode active material can be determined by crystal plane analysis of the carbon-based negative electrode active material such as X-ray diffraction. The alignment degree (OI) of the carbon-based negative electrode active material shown in the above formula 2 can be an indicator of the direction of alignment of the crystal structure of the carbon-based negative electrode active material, more specifically, the degree of alignment of the crystal plane representing the plane of the carbon-based negative electrode active material relative to the surface of the negative electrode collector in the X-ray diffraction (XRD) measurement. For example, when the negative electrode active layer is a carbon-based negative electrode active material including graphite, the X-ray diffraction measurement of the electrode sheet shows 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, 77.5±0.2°, which represent the (0,0,2), (1,0,0), (1,0,1)R, (1,0,1)H, (0,0,4), (1,1,0) surfaces of the crystal planes of the graphite contained in the negative electrode active layer.

[0138] Typically, in the case of graphite, graphene layers are placed on the a-axis and b-axis surfaces, and these graphene layers are stacked along the c-axis to have a hexagonal or rhombus crystal structure. Here, the crystal plane peak is a peak indicating the surface characteristics of such a crystal structure. In addition, it can be observed that the peak appearing at 2θ = 43.4 ± 0.2° is an overlap of the peaks corresponding to the (1,0,1)R surface of the carbon-based negative electrode active material and the (1,1,1) surface of the negative electrode collector such as copper (Cu), and can therefore be excluded when determining the degree of alignment.

[0139] The present disclosure can measure the degree of alignment (OI) of carbon-based negative electrode active materials by the ratio of the area of ​​the peak at 2θ=54.7±0.2° indicating the (0,0,4) surface to the peak at 2θ=77.5±0.2° indicating the (1,1,0) surface (specifically, the ratio of the area obtained by integrating the intensity of the peak). The (0,0,4) surface appearing at 2θ=54.7±0.2° indicates the thickness direction characteristics of the laminated structure of the stacked graphite layers, and the (1,1,0) surface appearing at 2θ=77.5±0.2° indicates the planar characteristics of the stacked graphite layers. Therefore, the smaller the peak of the (0,0,4) surface indicating the thickness direction characteristics of the graphite layer plane, the larger the peak of the (1,1,0) surface indicating the planar characteristics of the graphite layer, and the greater the alignment of the graphite plane relative to the surface of the negative electrode current collector at a high angle. In other words, the degree of alignment (OI) may mean that when the value is close to 0, the angle or slope of the plane of the graphite layer relative to the surface of the negative electrode collector is close to 90°, and when the value is larger, the angle or slope relative to the surface of the negative electrode collector is close to 0° or 180°.

[0140] For example, since the crystal planes of the carbon-based negative electrode active material contained in the negative electrode active layer are aligned at a high angle relative to the negative electrode current collector, the degree of alignment (OI) of the negative electrode according to the present disclosure can be 0.2 to 1.5, more specifically 0.2 to 1.2; 0.2 to 1.0; 0.2 to 0.8; 0.2 to 0.5; 0.4 to 0.7; 0.3 to 0.6; 0.4 to 0.9; 0.5 to 0.9; 0.6 to 1.0; 0.7 to 1.0; 0.9 to 1.2; or 0.8 to 1.1.

[0141] The alignment degree (OI) of the carbon-based negative electrode active material is 1.5 or less, which means that when the carbon-based negative electrode active material includes graphite, the crystal plane (meaning the plane of the graphite layer) is aligned so that it has a high angle / slope relative to the negative electrode collector, such as 60° or greater, 70° or greater, 70° to 90°, 80° to 90°, 65° to 85° or 70° to 85°.

[0142] In addition, the negative electrode active layer is characterized in that the rebound rate after rolling in the orientation of the carbon-based negative electrode active material is low. The rebound rate of the negative electrode active layer may refer to the rate of increase of the average thickness of the negative electrode active layer within a predetermined period relative to the average thickness of the negative electrode active layer just after rolling, and in some cases, the average density of the negative electrode active layer may be applied instead of the average thickness of the negative electrode active layer. This quantifies the degree of return to the original state after rolling, and the lower the value, the greater the improvement of the rebound phenomenon of the negative electrode active layer.

[0143] As an example, the average thickness increase rate of the negative electrode active layer of the negative electrode according to the present disclosure, based on the average thickness just after rolling, at room temperature (22±1°C) (in other words, the rebound rate after 2.5 hours) can be less than 4%, and more specifically, it can be 3% or less; 2% or less; or 1.5% or less.

[0144] As another example, the average thickness increase rate of the negative electrode active layer of the negative electrode according to the present invention based on the average thickness just after rolling (in other words, the rebound rate after 72 hours) rolled at room temperature (22±1°C) can be less than 10%, more specifically, it can be less than or equal to 9.5%; or less than or equal to 9%.

[0145] In addition, the negative electrode according to the present disclosure is characterized in that the rebound phenomenon of the negative electrode active layer is improved, and it not only has excellent structural stability but also has high density. Specifically, the density of the negative electrode active layer can be 1.2 g / cm 3 Up to 1.8g / cm 3 , and more specifically, the density of the negative electrode active layer can be 1.3 g / cm 3 Up to 1.8g / cm 3 ; 1.4g / cm3 Up to 1.8g / cm 3 ; 1.5g / cm 3 Up to 1.8g / cm 3 ; 1.4g / cm 3 Up to 1.7g / cm 3 ; or 1.45g / cm 3 Up to 1.65g / cm 3 .

[0146] In this case, the thickness of the negative electrode active layer is not particularly limited, but its average thickness may be 100 μm to 300 μm, and more specifically, its average thickness may be 100 μm to 250 μm; or 130 μm to 190 μm. The present disclosure adjusts the average thickness of the negative electrode active layer to the above range, so that the crystal planes of the carbon-based negative electrode active material can be uniformly aligned, thereby improving the high-rate charge and discharge performance and energy density of the battery including the negative electrode.

[0147] In addition, in addition to carbon-based negative electrode active materials, the negative electrode according to the present disclosure may also include a predetermined silicon-based negative electrode active material in the negative electrode active layer. Silicon-based negative electrode active materials are materials including silicon (Si) as a main component, and may include silicon (Si) particles, silicon monoxide (SiO), silicon dioxide (SiO2) particles, silicon carbide (SiC) or a mixture thereof. In some cases, in addition to silicon (Si) particles, silicon monoxide (SiO) and / or silicon dioxide (SiO2) particles, silicon (Si) particles may also include silicon carbide (SiC) particles.

[0148] In addition, based on 100 parts by weight of the overall negative electrode active material, the silicon-based negative electrode active material may be included in an amount of 0.5 to 30 parts by weight, and more specifically, 1 to 9 parts by weight, 3 to 7 parts by weight, 11 to 19 parts by weight, 13 to 17 parts by weight, 10 to 30 parts by weight, 20 to 30 parts by weight, 15 to 25 parts by weight, 9 to 22 parts by weight. The present disclosure can improve the charge capacity per unit mass while reducing lithium consumption and irreversible capacity loss during initial charge and discharge of the battery by adjusting the content of the carbon-based negative electrode active material and the silicon-based negative electrode active material included in the negative electrode active material to the range as described above.

[0149] In addition, in addition to including the carbon-based negative electrode active material as a main component, the negative electrode active layer may optionally include a conductor, a binder, other additives, etc. as needed.

[0150] The conductor may include, but is not limited to, one or more of carbon black such as acetylene black, Ketjen black, etc.; carbon nanotubes; carbon fibers; and the like.

[0151] As an example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., alone or in combination, as a conductor.

[0152] In this case, for a total of 100 parts by weight of the negative electrode active layer, the content of the conductor may be 0.1 to 10 parts by weight, and more specifically, the content may be 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 2 to 6 parts by weight, or 0.5 to 2 parts by weight. The present disclosure controls the content of the conductor within the range as described above, thereby preventing the problem of an increase in the resistance of the negative electrode due to a low content of the conductor, thereby reducing the charging capacity, and the problem of a reduction in the content of the negative electrode active material due to an excessive amount of the conductor, thereby reducing the charging capacity, or the problem of a reduction in the fast charging characteristics due to an increase in the load of the negative electrode active layer.

[0153] In addition, the binder can be suitably applied as a component that helps to connect the negative electrode active material and conductor with the current collector without deteriorating the electrical properties of the electrode, but more specifically, the binder may include any one or more of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR) and fluorinated rubber.

[0154] For a total of 100 parts by weight of the negative electrode active layer, the content of the binder may be 0.1 to 10 parts by weight, and more specifically, the content may be 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight. The present disclosure may control the content of the binder contained in the negative electrode active layer within the above range, thereby preventing the adhesiveness of the active layer from being reduced due to the low content of the binder or preventing the electrical characteristics of the electrode from being reduced due to an excessive amount of the binder.

[0155] In addition, according to the battery model or product use to which the negative electrode of the present disclosure is applied, the negative electrode active layer may have a structure in which two separate layers are stacked, but is not limited thereto.

[0156] Specifically, the negative electrode according to the present disclosure may have a structure in which a first negative electrode active layer is arranged on the negative electrode current collector and a second negative electrode active layer is arranged on the first negative electrode active layer. In this case, the first negative electrode active layer and the second negative electrode active layer each contain a carbon-based negative electrode active material, and the carbon-based negative electrode active materials contained in each layer may be the same or different. The advantage of the negative electrode active layer having a two-layer structure on the negative electrode current collector is that the composition of each negative electrode active layer can be easily controlled, so that the energy-efficient active material of the battery can be applied as the negative electrode active material to improve the electrical properties of the negative electrode and improve and / or prevent problems caused thereby (for example, the adhesion between the surface of the negative electrode current collector and the negative electrode active layer is reduced).

[0157] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, copper, stainless steel, nickel, titanium, calcined carbon, etc. can be used, and in the case of copper or stainless steel, a surface treated with carbon, nickel, titanium, silver, etc. can also be used. In addition, considering the conductivity and total thickness of the manufactured negative electrode, the average thickness of the above-mentioned negative electrode current collector can be appropriately applied to be 1 μm to 500 μm.

[0158] Lithium secondary battery

[0159] In one embodiment, the present disclosure also provides

[0160] A lithium secondary battery includes an electrode assembly, the electrode assembly including a positive electrode, the negative electrode of the present disclosure as described above, and a separator disposed between the positive electrode and the negative electrode.

[0161] In this case, the negative electrode has the same configuration as described above, and thus a detailed description is omitted.

[0162] In addition, the positive electrode includes a positive electrode active material layer prepared by applying, drying and pressing a slurry including a positive electrode active material on a positive electrode collector, and the positive electrode active material layer may optionally further include a conductor, a binder, other additives, etc. as needed.

[0163] The positive electrode active material may include one or more of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 that can electrochemically react (reversibly intercalate and deintercalate lithium ions) on a positive electrode current collector:

[0164] [Chemical formula 1]

[0165] Li x [Ni y Co z Mn w M 1 v ]O2

[0166] [Chemical Formula 2]

[0167] LiM 2 p Mn q P r O4

[0168] In Chemical Formulas 1 and 2,

[0169] M 1 is at least one element selected from W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo,

[0170] x, y, z, w, and v are respectively 1.0 ≤ x ≤ 1.30, 0.5 ≤ y < 1, 0 < z ≤ 0.3, 0 < w ≤ 0.3, and 0 ≤ v ≤ 0.1, where y + z + w + v = 1,

[0171] M 2 is Ni, Co, or Fe; and

[0172] p is 0.05 ≤ p ≤ 1.0, and

[0173] q is 1 - p or 2 - p, and

[0174] r is 0 or 1.

[0175] The lithium metal oxides represented by the above Chemical Formulas 1 and 2 are materials with high contents of nickel (Ni) and manganese (Mn) respectively, and when used as the positive electrode active material, compared with the conventionally used positive electrode active materials such as lithium iron phosphate (LiFeO4), etc., it has the advantage of providing a more stable supply of high - capacity and / or high - voltage electricity.

[0176] In this case, the lithium metal oxide represented by Chemical Formula 1 may include LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2, LiNi0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc., and the lithium metal oxide represented by Chemical Formula 2 may include LiNi 0.7 Mn 1.3 O4; LiNi 0.5 Mn 1.5 O4; LiNi 0.3 Mn 1.7 O4, LiFePO4, LiFe 0.7 Mn 0.3 PO4, etc.

[0177] In addition, the positive electrode active material may be included in at least 85 parts by weight of the positive electrode active material layer, and more specifically, it may be included in at least 90 parts by weight, at least 93 parts by weight, or at least 95 parts by weight.

[0178] Furthermore, the positive electrode active material layer may further include a conductor, a binder, other additives, and the like in addition to the positive electrode active material.

[0179] In this case, the conductor material is used to improve the electrical properties of the positive electrode, and those conventionally used in the art can be applied, but specifically can include one or more of natural graphite, artificial graphite, carbon black, acetylene black, denkablack, Ketjen black, super black (super-P), channel black, furnace black, lamp black, thermal black, graphene and carbon nanotubes.

[0180] In addition, based on the weight of each positive electrode active material, 0.1 to 5 parts by weight of the conductor may be included, and more specifically, 0.1 to 4 parts by weight; 2 to 4 parts by weight; 1.5 to 5 parts by weight; 1 to 3 parts by weight; 0.1 to 2 parts by weight; or 0.1 to 1 part by weight of the conductor may be included.

[0181] In addition, the binder plays the role of binding the positive active material, the positive electrode additive and the conductor to each other, and can be used without particular limitation, as long as it has such a function. Specifically, the binder may include one or more resins selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate and copolymers thereof. In one example, the binder may include polyvinylidene fluoride.

[0182] In addition, the binder may be included in an amount of 1 to 10 parts by weight, more specifically, 2 to 8 parts by weight; or 1 to 5 parts by weight, per weight of the positive electrode active material.

[0183] The total thickness of the positive electrode active layer is not particularly limited, but may be 50 to 300 μm, more specifically, 100 to 200 μm; 80 to 150 μm; 120 to 170 μm; 150 to 300 μm; 200 to 300 μm; or 150 to 190 μm.

[0184] In addition, as the positive electrode, a positive electrode current collector having high conductivity without causing chemical changes in the battery can be used. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used, and in the case of aluminum or stainless steel, surface treatment with carbon, nickel, titanium, silver, etc. can be used. In addition, considering the conductivity and total thickness of the manufactured positive electrode, the average thickness of the current collector can be appropriately applied to be 3 μm to 500 μm.

[0185] In addition, the separator interposed between the positive electrode and the negative electrode of each unit cell is an insulating film with high ion permeability and high mechanical strength, and may be any polymer conventionally used in the art, but is not particularly limited thereto, and may include one or more polymers selected from polypropylene; polyethylene; and polyethylene-propylene copolymer having chemical resistance and hydrophobicity. The separator may have the form of a porous polymer substrate such as a sheet or a non-woven fabric including the above-mentioned polymer, and in some cases, it may also have the form of a composite separator in which organic or inorganic particles are coated on a porous polymer substrate by an organic binder. In addition, the separator may have an average pore diameter of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.

[0186] In addition, the lithium secondary battery according to the present disclosure may be in the form of a secondary battery, which may include a stacked; zigzag; or zigzag stacked electrode assembly but this is not particularly limited. As an example, the lithium secondary battery according to the present disclosure may be a pouch-type secondary battery or a prismatic secondary battery.

[0187] Hereinafter, the present disclosure will be described in more detail through examples and experimental examples.

[0188] However, the following examples and experimental examples are merely illustrative of the present disclosure, and the present disclosure is not limited to the following examples and experimental examples.

[0189] Examples 1 to 4 and Comparative Examples 1 to 6. Manufacturing of Negative Electrode of Lithium Secondary Battery

[0190] First, natural graphite and artificial graphite are prepared as carbon-based negative electrode active materials, respectively, and negative electrode slurry is prepared using the prepared carbon-based negative electrode active materials.

[0191] Specifically, the negative electrode active material was prepared by mixing natural graphite and artificial graphite in a weight ratio of 1-3:7-9 and using carbon black as a conductor and carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) as a binder. Then, the negative electrode slurry was prepared by mixing 95 parts by weight of the mixed graphite, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethyl cellulose (CMC) and 2.5 parts by weight of styrene butadiene rubber (SBR) with water so that the solid content was 50%.

[0192] Once the negative electrode slurry was prepared, it was cast on a copper sheet (thickness: 10 μm) using a die coater, which was conveyed by roll-to-roll (conveying speed: 5 m / min). At this time, the average thickness of the cast negative electrode slurry was controlled to 200 μm.

[0193] Then, a permanent magnet was placed on the upper portion of the applied negative electrode slurry and the lower portion of the negative electrode current collector, and a magnetic field was applied for 15 to 30 seconds, and the negative electrode slurry was thermally dried to form a negative electrode active layer (density: 1.5±0.05 g / cm 3 ). At this time, as shown in Table 1 below, the intensity of the magnetic field applied to the negative electrode slurry was adjusted, and X-ray diffraction spectroscopy (XRD) was performed on the negative electrode active layer to measure the spectrum. The measurement conditions of X-ray diffraction (XRD) were as follows:

[0194] -Target: Cu (Kα ray) graphite monochromator

[0195] - Slits: Divergence slit = 1°, Receiving slit = 0.1 mm, Scattering slit = 1°,

[0196] -Measurement area: (1,1,0) surface: 76.5°<2θ<78.5° / (0,0,4) surface: 53.0°<2θ<57.0°.

[0197] From the spectrum measured under the above conditions, the corresponding areas of the peak indicating the (0,0,4) crystal plane and the peak indicating the (1,1,0) crystal plane were obtained, and the ratio of these areas (I 004 / I 110 ) to obtain the degree of alignment (OI) of the hybrid graphite by region. The calculated values ​​are shown in Table 1 below.

[0198] Subsequently, a negative electrode of a lithium secondary battery was prepared by rolling the active layer at a conveying speed of 3 m / s at 22±1° C. At this time, the rolling load of the negative electrode active layer was adjusted as shown in Table 1 below.

[0199] [Table 1]

[0200] Magnetic field strength [G] Rolling load [tons] OI Does it satisfy formula 1? Example 1 3500 5.255 1.34 O Example 2 4000 5.075 1.04 O Example 3 6250 4.895 0.44 O Example 4 8050 4.750 0.39 O Comparative Example 1 - 5.000 6.98 X Comparative Example 2 - 9.000 8.21 X Comparative Example 3 3500 2.500 1.29 X Comparative Example 4 3500 7.000 1.63 X Comparative Example 5 8050 2.000 0.36 X Comparative Example 6 8050 6.500 0.75 X

[0201] Examples 5 to 8 and Comparative Examples 7 to 12. Fabrication of Lithium Secondary Batteries

[0202] By preparing LiNi with a particle size of 5 μm 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 was used as the positive electrode active material, and was mixed with polyvinylidene fluoride as a carbon-based conductive agent and a binder in a weight ratio of 94:3:3 in N-methylpyrrolidone (NMP) to form a slurry, which was cast on an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to prepare a positive electrode.

[0203] A separator including 18 μm polypropylene was interposed between the positive electrode obtained above and the negative electrodes prepared in Examples 1 to 4 and Comparative Examples 1 to 6, respectively, and a lithium secondary battery was assembled by inserting it into a case and then injecting an electrolyte component.

[0204] At this time, the type of negative electrode applied to each lithium secondary battery is indicated in Table 2 below.

[0205] [Table 2]

[0206] Type of cathode used Example 5 Negative electrode prepared in Example 1 Example 6 Negative electrode prepared in Example 2 Example 7 Negative electrode prepared in Example 3 Example 8 Negative electrode prepared in Example 4 Comparative Example 7 The negative electrode prepared in Comparative Example 1 Comparative Example 8 The negative electrode prepared in Comparative Example 2 Comparative Example 9 The negative electrode prepared in Comparative Example 3 Comparative Example 10 The negative electrode prepared in Comparative Example 4 Comparative Example 11 The negative electrode prepared in Comparative Example 5 Comparative Example 12 The negative electrode prepared in Comparative Example 6

[0207] Experimental example

[0208] The following experiments were performed to evaluate the performance of the negative electrode according to the present disclosure.

[0209] a) Rebound improvement effect of negative electrode active layer

[0210] The negative electrode was prepared by performing the same method as in Examples 1 to 4 and Comparative Examples 1 to 6, but the average thickness and density of the negative electrode active layer were measured just after rolling. Then, the manufactured negative electrode was stored at room temperature (22±1°C) for 120 hours, and the average thickness of the negative electrode active layer was measured after 0.5 hours, 1 hour, 2.5 hours, 24 hours, 48 ​​hours, and 72 hours.

[0211] From the results of the measurement, the average thickness increase rate of the negative electrode active layer just after rolling was calculated and determined as the springback rate of the negative electrode active layer. The results are shown in Table 3 below.

[0212] b) Lifespan characteristics evaluation

[0213] For the lithium secondary batteries prepared in Examples 5 to 8 and Comparative Examples 7 to 12 (having negative electrodes of Examples 1 to 4 and Comparative Examples 1 to 6, respectively), the capacity (1 cycle capacity) was measured when the lithium secondary battery was buffered (SOC 100%) at a rate of 0.5C at room temperature (22±1°C) and the buffered lithium secondary battery was discharged to 1.5V at a rate of 0.1C. Then, each lithium secondary battery was charged at a rate of 0.5C (SOC 100%) and discharged to 1.5V at a rate of 1.0C for 200 cycles, and the capacity (200 cycle capacity) of the recharged lithium secondary battery when discharged to 1.5V at a rate of 0.1C was measured. Based on the measured 1 cycle capacity, the discharge capacity retention rate of the capacity after 100 cycles was calculated, and the results are shown in Table 3 below.

[0214] [Table 3]

[0215]

[0216] As shown above in Table 3, it can be observed that the negative electrode of the lithium secondary battery according to the present disclosure has a significantly improved springback phenomenon of the negative electrode active layer after rolling, and the structural stability of the negative electrode active layer is improved, resulting in an increased lifespan.

[0217] Specifically, the negative electrode according to the example (in which the rolling load was controlled according to Formula 1 after applying a magnetic field to the negative electrode slurry according to the present disclosure) exhibited an improved rebound phenomenon of the negative electrode active layer, so that the rebound rate 2.5 hours after rolling was found to be 2% or less, and the rebound rate 72 hours after rolling was found to be less than 10%. In addition, the negative electrode of the example has an improved structural stability of the negative electrode active layer, so that even after 100 charge and discharge cycles, the discharge capacity retention rate was found to be 89% or more.

[0218] On the other hand, it was found that the thickness of the negative electrode active layer of the comparative example (in which rolling was performed without applying a magnetic field or after applying a magnetic field with a load that did not satisfy Formula 1 of the present disclosure) increased significantly 1 hour after rolling. Specifically, the rebound rate 2.5 hours after rolling was 6% or more, and the rebound rate 72 hours after rolling exceeded 10%. In addition, it was found that the discharge capacity retention rate of the negative electrode of the comparative example after 100 charge and discharge cycles was less than 85%, which was due to the low structural stability of the negative electrode active layer.

[0219] It can be seen from these results that the manufacturing method according to the present disclosure can significantly improve the rebound phenomenon of the negative electrode active layer by the following steps: drying and rolling the negative electrode slurry under the condition of applying a magnetic field, but controlling the rolling load according to Formula 1 which depends on the strength of the magnetic field applied to the negative electrode slurry, so that the rebound phenomenon of the negative electrode active layer can be significantly improved with a simple and small number of processes. In addition, the negative electrode thus prepared not only exhibits a high energy density while maintaining the target thickness, but also has the advantages of low rolling stress and improved structural stability of the negative electrode active layer, thereby reducing the volume change of the negative electrode active layer with charging and discharging, thereby improving the life of the battery.

[0220] As above, the present disclosure has been described in more detail through the drawings and embodiments. However, since the configuration described in the drawings or embodiments described herein is only one embodiment of the present disclosure and does not represent the entire technical spirit of the present disclosure, it should be understood that the present disclosure covers various equivalent forms, modified forms and replacement forms when submitting this application.

[0221] Therefore, the technical scope of the present disclosure is not limited to the contents described in the specific embodiments of the specification, but must be determined by the claims of the patent.

Claims

1. A method for manufacturing a negative electrode of a lithium secondary battery, the method comprising the following steps: applying a magnetic field to the negative electrode slurry applied to the negative electrode current collector; drying the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; and The negative electrode active layer formed by rolling, Wherein, the negative electrode slurry includes a carbon-based negative electrode active material, wherein the magnetic field is applied at a strength of 3,000G to 15,000G, The rolling load during rolling is controlled according to the following formula 1: [Formula 1] y=Ax+B In formula 1, y represents the rolling load (unit: tons), x indicates the magnetic field strength when the magnetic field is applied (unit: Gauss), A and B are -0.01≤A<0 and 3≤B≤7.

2. The method for manufacturing a negative electrode of a lithium secondary battery according to claim 1, wherein: The rolling load is 1 ton to 7 tons.

3. The method for manufacturing a negative electrode of a lithium secondary battery according to claim 1, wherein: The rolling comprises: a first rolling, in which the formed negative electrode active layer is pressurized using the rolling load of [Formula 1]; and A second rolling, in which the negative electrode active layer after the first rolling is further pressurized, wherein the rolling load of the first rolling is greater than the rolling load of the second rolling.

4. The method for manufacturing a negative electrode of a lithium secondary battery according to claim 3, wherein: The rolling load during the second rolling is a ratio of 50% or less of the rolling load during the first rolling.

5. The method for manufacturing a negative electrode of a lithium secondary battery according to claim 1, wherein: The rolling is performed at a temperature of 20°C to 35°C.

6. The method for manufacturing a negative electrode of a lithium secondary battery according to claim 1, wherein: The negative electrode active layer had an average thickness increase rate of less than 10% after rolling for 72 hours at room temperature based on the average thickness just after rolling.

7. The method for manufacturing a negative electrode of a lithium secondary battery according to claim 1, wherein: The step of applying the magnetic field is performed for 5 seconds to 60 seconds.

8. A negative electrode of a lithium secondary battery manufactured by the method for manufacturing a negative electrode of a lithium secondary battery according to claim 1, the negative electrode of the lithium secondary battery comprising: Anode current collector; as well as A negative electrode active layer is disposed on at least one surface of the negative electrode current collector and includes a carbon-based negative electrode active material.

9. The negative electrode of the lithium secondary battery according to claim 8, wherein: The negative electrode active layer has an alignment degree (OI) of a carbon-based negative electrode active material represented by Formula 2, and the alignment degree is 0.2 to 1.5: [Formula 2] OI=I 004 / I 110 In formula 2, I 004 indicates the area of ​​the peak representing the (0,0,4) crystal plane in the X-ray diffraction spectrum measurement of the negative electrode active layer, and I 110 Indicates the area of ​​the peak representing the (1,1,0) crystal plane in the X-ray diffraction spectrum measurement of the negative electrode active layer.

10. The negative electrode of the lithium secondary battery according to claim 8, wherein The rebound rate of the negative electrode active layer is less than 10%.

11. The negative electrode of the lithium secondary battery according to claim 8, wherein The average thickness of the negative electrode active layer is 100 μm to 300 μm.

12. The negative electrode of the lithium secondary battery according to claim 8, wherein The density of the negative electrode active layer is 1.2 g / cm 3 Up to 1.8g / cm 3 .

13. The negative electrode of the lithium secondary battery according to claim 8, wherein: The carbon-based negative electrode active material included in the negative electrode active layer includes at least one of natural graphite and artificial graphite.

14. The negative electrode of the lithium secondary battery according to claim 8, wherein The negative electrode active layer also includes a silicon-based negative electrode active material. The silicon-based negative electrode active material includes Si, SiC and SiO x At least one of , wherein 0.8≤x≤2.5.

Citation Information

Patent Citations

  • Temperature control apparatus for an electrical mat

    KR1020230032292A